Study on climatic quality evaluation technology of Dali Dongzao in Shaanxi based on meteorological factors - SHEN Jiaojiao; DANG Chaoqi; ZHANG Yuefan; GUO Qi; WANG Jingzhong (Guoshu xuebao, 2025)
[Objective] With the expansion of planting areas and increased yields of Dali Dongzao (Ziziphus jujuba ‘Dongzao’) in Shaanxi, the quality of Dali Dongzao has become inconsistent. There is an urgent need to shift the focus from quantity-driven efficiency to quality-oriented efficiency. Under the same field management, the crop quality of a variety is primarily influenced by climatic conditions. The evaluation of crop climate quality could assess the extent to which weather and climate conditions impact crop quality. The establishment of climate quality evaluation model of Dali Dongzao could provide technical guidance for objective evaluation and prediction of the climate quality of Dali Dongzao, which would be of great significance for improving the quality of the fruit and enhancing the market competitiveness. [Methods] Based on the daily meteorological data of Dali from 1991 to 2024 and years of quality inspection results, the key growth stages and weight coefficients affecting the climate quality of Dali Dongzao were determined by field investigation and expert decision method. The SPSS 26 was used to analyze the trend and significance of meteorological factors in the key growth stages of Dali Dongzao from 1991 to 2024. According to the quantitative grade evaluation standard of agro-meteorological standard, the suitability of climate quality evaluation indexes was divided into four grades: 3, 2, 1 and 0, representing the most suitable, suitable, fairly suitable and general, respectively. At the same time, the threshold ranges of four different grades of key meteorological assessment indicators were graded by the percentile method. On the basis of the ecological suitability theory, the climate quality evaluation model of Dali Dongzao was established by weighted index summation method, and the climate quality index (ICQ) was divided into four grades: excellent, good, fair, and poor. For ease of comparison, each of quality indices were graded into four grades, corresponding with the four grades of ICQ. Through the typical-year verification method, the grade results of the model were compared with the actual quality grade. If the grades were consistent, it meant that the model was scientific and reasonable; if the grades were different by one level or more, it meant that the model should be further optimized and adjusted. [Results] The flowering stage, fruit expansion stage and ripening stage were the key growth stages which would affect the quality of Dali Dongzao. Analysis revealed that the average temperature and accumulative rainfall during the three stages all showed no obvious change or weak upward trend (none of which passed p<0.05 significance test), while the sunshine duration showed a downward trend (the downward trends during the fruit expansion stage and ripening stage passed p<0.05 and p<0.01 significance tests, respectively). The relative humidity at flowering stage, sunshine duration at fruit expansion stage, diurnal temperature range at ripening stage, sunshine duration at ripening stage and accumulative rainfall at ripening stage were the five key meteorological evaluation indexes affecting the quality of Dali Dongzao. The model was developed with the five indexes using the weighted index summation method, and ICQ was categorized into four grades: excellent (>1.8), good (>1.2-1.8), fair (1.0-1.2), and poor (<1.0). The three key indicators—single fruit weight, soluble solids content, and vitamin C content—were selected as quality indices for evaluating the climate quality of Dali Dongzao. By comparing and verifying the model evaluation results with the actual quality inspection results in 2019, 2023, and 2024, it was found that the suitability of the key meteorological factors during the flowering period, fruit expansion period and maturity period in 2019 was 0.9, 0.4 and 0.8 respectively, and the ICQ was 2.1, falling into the “excellent” category. The soluble solids and vitamin C contents were 36.9% and 4.88 mg·g-1, respectively, and the single fruit weight was 18.9 g, all of them falling into the “excellent” category, too. In 2023, the suitability of key meteorological factors at flowering, fruit expansion and ripening stages were 0.9, 0.4 and 0.6, respectively, and the ICQ was 1.9, falling into the “excellent” category. The contents of soluble solid and vitamin C were 33.2% and 3.78 mg·g-1, respectively, and the single fruit weight was 24.7 g, all of them falling into the “excellent” category, too. In 2024, the ICQ was 1.5, falling into the “good” category, at the same time, the contents of soluble solid and vitamin C were 22.2% and 3.28 mg·g-1, respectively, and the single fruit weight was 18.5 g, all of them falling into the “good” category, too. In summary, the outcomes of the climate quality evaluation model developed in this study were in alignment with the quality inspection results, thereby providing an objective assessment of the role of the meteorological conditions impacting the quality of Dali Dongzao. From 1991 to 2024, the proportion of years with climate quality rated as “excellent” and “good” was 82.4%. [Conclusion] Based on the meteorological data and quality inspection results, this study established a climate quality evaluation model for Dali Dongzao and classified the ICQ into four grades. The typical-year verification results showed that the model and the classification results were consistent with the actual production, which would provide a technical support for the objective evaluation and prediction of the climate quality of Dali Dongzao. However, it should be necessary to accumulate longterm quality inspection data to further optimize the model in the future.